Implementasi Pendidikan Karakter Kedisiplinan Pada Siswa Madrasah Ibtidaiyah Pesa Kecamatan Wawo Kabupaten Bima - Mulyadin (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
This research aims to find out the implementation of Discipline character education in Madrasah Ibtidaiyah Pesa Students, Wawo District, Bima Regency, This type of research is using qualitative research conducted through direct observation in the field which is used as the object of research, research to study and examine the phenomena that occur, The data sources in this study include Primary data sources of Principals and Teachers, and Parents of Students at Madrasah Ibtidaiya Pesa Wawo, and Secondary Data Archives, Documents in Madrasah Ibtidaiyah Pesa, Wawo District. Character development of Student Discipline must be carried out as early as possible, considering that globalization increasingly threatens the morale of our sons and daughters by encroaching on various aspects of life. Therefore, the revitalization of character education in which there is a character of discipline is appropriate and even should be included in a curriculum design and learning process, school/madrasah culture, and many self-development and extracurricular programs for students in Madrasah.